PENGALAMAN BULLYING DAN RESILIENSI AKADEMIK: STUDI DESKRIPTIF PADA SISWA SMP NASIONAL KOTA BANDUNG - Yoseptry, Ricky; Mulyanawati, Cucu; Paridah, Didah; Aviani, Doris; Sriwulan, Permanik Ahni; Rahayu Rahmadina, Sekar Putri (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
This study aims to describe the bullying experiences experienced by students and their relationship to improving academic achievement at SMP Nasional Bandung City. This study uses a descriptive qualitative approach with a phenomenological design. Data were collected through in-depth interviews, observations, and documentation. The results of the study indicate that the forms of bullying that occur include verbal, physical, social, and cyberbullying. The school does not yet have a special anti-bullying program, but has intervened through counseling services and educational coaching. Several victims of bullying showed an increase in academic achievement as a form of resilience to social pressure. Supporting factors for this success include emotional support, teacher and parent involvement, and positive activities at school.